Annotated index of Tula Dula scripts from 1977-2017 - Coloma, Wynonah Charise I. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Tula Dula are short stage plays that were written by scriptwriters to pepict the story and life cycle/struggles most Iskolar ng Bayan faced. This paper aims to zero in on which themes were prevalently used by scriptwriters.